Inhibitory effects of antibiofilm compound 1 against Staphylococcus aureus biofilms. (March 2016) - Shrestha, Looniva; Kayama, Shizuo; Sasaki, Michiko; Kato, Fuminori; Hisatsune, Junzo; Tsuruda, Keiko; Koizumi, Kazuhisa; Tatsukawa, Nobuyuki; Yu, Liansheng; Takeda, Kei; Sugai, Motoyuki
ABSTRACT: A novel benzimidazole molecule that was identified in a small‐molecule screen and is known as antibiofilm compound 1 (ABC‐1) has been found to prevent bacterial biofilm formation by multiple bacterial pathogens, including Staphylococcus aureus, without affecting bacterial growth. Here, the biofilm inhibiting ability of 156 μM ABC‐1 was tested in various biofilm‐forming strains of S. aureus . It was demonstrated that ABC‐1 inhibits biofilm formation by these strains at micromolar concentrations regardless of the strains' dependence on Polysaccharide Intercellular Adhesin (PIA), cell wall‐associated protein dependent or cell wall‐ associated extracellular DNA (eDNA). Of note, ABC‐1 treatment primarily inhibited Protein A (SpA) expression in all strains tested. spa gene disruption showed decreased biofilm formation; however, the mutants still produced more biofilm than ABC‐1 treated strains, implying that ABC‐1 affects not only SpA but also other factors. Indeed, ABC‐1 also attenuated the accumulation of PIA and eDNA on cell surface. Our results suggest that ABC‐1 has pleotropic effects on several biofilm components and thus inhibits biofilm formation by S. aureus .